Development of an individual-based simulation model of multiple-species mangrove forests - Estacio, Ian C.
To ensure that mangrove forest conservation efforts are successful, simulation models of mangrove forests are developed to forecast outcomes of different environmental scenarios. This research presents MaDS (Mangrove species Dominance Simulator), an individual-based model that simulates the structures of mixed mangrove forest stands by considering specific responses of mangrove species to shading, salinity, and inundation frequencies. By simulating certain inundation and salinity conditions in a 50 m x 50 m plot, the model forecasts the resulting dominance of different mangrove species. The model uses a modified Field of Neighborhood (FON) approach where species-specific shading tolerances are considered in the computation of competition response. The salinity response considers the species-specific upper-boundary salinity value of optimum growth and the species-specific maximum porewater salinity value. The inundation response considers that the limit inundation frequency that a mangrove tree can tolerate is a function of the species-specific maximum inundation frequency and the current salinity condition it senses. Simulations of different test sites in Katunggan It-Ibajay (KII) Eco-park, Aklan, Philippines given actual site salinity and inundation frequency values showed simulated dominant species matched with dominant species in the sites given that different groups of species are tested. Simulation of mixed mangrove forests stands showed forest dynamics observed in mangrove forests, such as lack of understory trees, rise of new dominating trees in forests gaps, and the total forest above-ground biomass reaching a limit. Simulation results also showed the different abundances of species for different combinations of salinity and inundation frequency values. Results of the simulations imply that observed zonation in mangrove forests is not only caused by the environmental conditions in the site but also by the number and characteristics of species in the site.